Comparison and the effect of selected insecticide against thrips on Capsicum annum / Nuratiqah Hamzah - Hamzah, Nuratiqah (Faculty of Plantation and Agrotechnology, 2018)
This study focuses on Scirtothrips dorsalis, thrips (Thysanoptera: Thripidae) population on the Capsicum annum, chili treated with selected insecticide treated on in order to determine the efficacy of different insecticides. Four treatments (Three insecticides + control) were applied once a week for six weeks cropping period with three different modes of insecticides namely Malathion (Contact insecticide), Imidacloprid (Systemic insecticide) and Soursop (Bio-insecticide). The experimental plots were designed with Randomized Complete Block Design (RCBD) consisted six blocks as a repetition and each block had three replicates and the data were collected weekly. For the findings, there was significant difference of thrips population among treatments for the whole cropping period. Extracted leaves of Soursop was found to be the most effective in controlling with the least mean number of thrips followed by Malathion and Imidacloprid. Bio-insecticide was found to be good potential in controlling thrip and further study should be carried out to be more effective and reliable.